Performance evaluation of acetylcholinesterase-based biosensors for detection of heavy metals - David, Melinda; Badea, Mihaela; Florescu, Monica (Univerzita Pardubice, 2011)
In this work, mediated carbon-ink screen-printed electrodes are used to develop enzyme-based biosensors for detection of selected heavy metals. Two immobilisation methods were used for acetylcholinesterase (AChE) immobilisation on electrode surface together with two redox mediators. The methods used for the encapsulation of the enzyme were: cross-linking with bi-functional reagents like glutar-aldehyde (GA) and encapsulation with sol-gel method.The used mediators were TCNQ (tetracianoquinodimethan) and CoPC (cobalt phthalocyanine). Comparison between biosensors performance was made function of electrolyte pH, especially for more acidic values were heavy metals are present in ionic form.
Keywords: biosensors; screen-printed electrodes; acetylcholinesterase; heavy metals